Kajian Meta Analisis: Meningkatkan Hasil Belajar Siswa sekolah dasar Dengan Model Problem Based Learning - Mitha Olivia; Dea Ananda; Endang Indarini (Papanda Publisher, 2022)
Education is a very important thing for humans which aims to humanize humans and make the abilities and qualities possessed by humans to be superior and advance the life of the nation. The purpose of this study is to determine whether the Problem Based Learning Model from several published meta-analytical studies can have an effect on improving the learning outcomes of elementary school students. This study uses a type of meta-analysis research. The results of the Effect Size test prove that the Problem Based Learning model has a small effect on improving the learning outcomes of elementary school students. In addition, the results of the Ancova Problem Based Learning model have an average value of 80,0800. So it can be concluded that the Problem Based Learning learning model is effective if applied in improving the learning outcomes of elementary school students.